Pobočja etične pietete in idealiziranih procedur v etnoloških raziskavah - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 1998)
The autor reflects on the possibility of establishing professional ethics in ethnology and especially on ethics in collecting life stories. Foreign experience and ethical dilemmas are compared domestic ones, especially with those gathered in Carinthia (Austria) in the course of collecting material for a series of volumes entitled "The way we lived: life stories of Carinthian Slovenes." The article deals woth general ethical questiones in ethnology like the ethnologist's responsibility to the narrator, his responsibility to other ethnologists in the context of teamwork, and his responibiliy to the sponsors of the research. These topics are examined in the area of life stories with emphasis on the first mentioned responsibility and based on the author's own field experience and that of others. In the process the author also tackels the role of ethnologists in the field work, the voluntary collaboration of the narrator or his consent, the privacy of personal information, moral and other damages, copyright issues, anonymity and possible libel.
Keywords: ethnology; etnologija; raziskovalno delo; raziskave; etika; ethics; spoštovanje